Twin Anemia Polycythemia Sequence: A Complication of Monochorionic Diamniotic Twin Gestation [16P]. (May 2017) - Savasan, Zeynep Alpay; Zeb, Amna; Scott, Lauren
Abstract : INTRODUCTION: Twin anemia polycythemia sequence (TAPS) is an important prenatal complication of monochorionic twin gestations due to abnormal placental vascular anastomosis. Prenatal ultrasound is the only screening modality. Our objective was to evaluate the prediction potential of current prenatal ultrasound screening in diagnosing TAPS in monochorionic diamniotic twin gestations. METHODS: Maternal and neonatal medical records were reviewed for women with monochorionic diamniotic twins who delivered at Beaumont Hospital System (Royal Oak and Troy) from 2009-2014. Available prenatal ultrasound findings were compared with the neonatal outcomes. Postnatal TAPS diagnosis was confirmed with neonatal peripheral blood hemoglobin values. RESULTS: A total of 132 maternal charts were reviewed and 102 were used in data collection. The median maternal age was 31 years (19-45) with a median parity of 1 (0-3). Among these women 10% (n=10) had assisted reproductive technology. Median gestational age at time of delivery was 35.4 weeks (20.7-39). Median NICU stay for twin A and twin B were 9 (0-264) and 8.5 days, (0-103), respectively. Among 132 prenatal ultrasound screenings, 26% (n=32) were reported as abnormal. Thirty-three percent (n=34) of the neonates were diagnosed with anemia and polycythemia; of these neonates 29% (n=30) had anemia, 4% (n=4) had polycythemia. The sensitivity and specificity of prenatal ultrasound in the prediction of TAPS was 26% (95% CI: 13-44) and 77% (95% CI: 65-87), respectively. CONCLUSION: Current prenatal ultrasound screening guidelines have low sensitivity and specificity in predicting TAPS in monochorionic diamniotic twin gestations. New and updated prenatal screening methods may improve TAPS prediction.